Adults With Incident Accelerated Knee Osteoarthritis Are More Likely to Use Pharmacological Treatment Options and Receive Arthroscopic Knee Surgery: Data From the Osteoarthritis Initiative. Issue 6 (25th July 2019) - Davis, Julie E.; Harkey, Matthew S.; Liu, Shao‐Hsien; Lapane, Kate; Price, Lori Lyn; Lu, Bing; Lo, Grace H.; Eaton, Charles B.; Barbe, Mary F.; McAlindon, Timothy E.; Driban, Jeffrey B.
Abstract : Objective: To determine if people with incident accelerated knee osteoarthritis (AKOA) were more likely to receive a pharmacological treatment or arthroscopic knee surgery than those with typical knee osteoarthritis (KOA) or no KOA. Methods: We conducted a nested cohort study using data from baseline and the first 8 years of the Osteoarthritis Initiative. Eligible participants had no radiographic KOA at baseline (Kellgren‐Lawrence [KL] < 2). We classified three groups using KL grades: 1) AKOA: knee progressed to advanced‐stage KOA (KL 3/4) in 4 years or less, 2) typical KOA: knee increased in KL grade by 8 years (excluding AKOA), and 3) No KOA: no change in KL grade by 8 years. The outcome was self‐reported arthroscopic knee surgery or a pharmacological treatment option: nonsteroidal anti‐inflammatory drugs (NSAIDs), hyaluronic acid injections, intra‐articular corticosteroid injections, or prescription analgesics. Between‐group differences in therapeutic use were evaluated with Chi‐square tests. Results: Adults who developed AKOA (n = 92) were more likely to report arthroscopic knee surgery (AKOA: 32%, KOA [n = 380]: 8%, no KOA [n = 875]: 3%; P < 0.001), hyaluronic acid injections (AKOA: 10%, KOA: 4%, no KOA: 1%; P < 0.001), intra‐articular corticosteroid injections (AKOA: 30%, KOA: 7%, no KOA: 4%; P < 0.001), and NSAID use (over the counter: AKOA: 65%, KOA: 48%, and no KOA: 46%; P = 0.003; prescription: AKOA: 61%, KOA: 43%, no KOA: 41%; P = 0.002). Conclusion: Adults with AKOA are more likely to receive pharmacological treatment or arthroscopic knee surgery than their peers. Adults with AKOA are an important patient population that is understudied in clinical research despite their use of greater health care resources.